A Comprehensive Craniofacial Study of 22q11.2 Deletion Syndrome. (November 2017) - Lewyllie, A.; Roosenboom, J.; Indencleef, K.; Claes, P.; Swillen, A.; Devriendt, K.; Carels, C.; Cadenas De Llano-Pérula, M.; Willems, G.; Hens, G.; Verdonck, A.
The 22q11.2 deletion syndrome (22q11.2DS) is one of the most frequent microdeletion syndromes and presents with a highly variable phenotype. In most affected individuals, specific but subtle facial features can be seen. In this observational study, we aim to investigate the craniofacial and dental features of 20 children with a confirmed diagnosis of 22q11.2DS by analyzing 3-dimensional (3D) facial surface scans, 2-dimensional (2D) clinical photographs, panoramic and cephalometric radiographs, and dental casts. The 3D facial scans were compared to scans of a healthy control group and analyzed using a spatially dense geometric morphometric approach. Cephalometric radiographs were digitally traced, and measurements were compared to existing standards. Occlusal and dental features were studied on dental casts and panoramic radiographs. Interestingly, a general trend of facial hypoplasia in the lower part of the face could be evidenced with the 3D facial analysis in children with 22q11.2DS compared to controls. Cephalometric analysis confirmed a dorsal position of the mandible to the maxilla in 2D and showed an enlarged cranial base angle. Measurements for occlusion did not differ significantly from standards. Despite individual variability, we observed a retruded lower part of the face as a common feature, and we also found a significantly higher prevalence of tooth agenesis in our cohort of 20 children with 22q11.2DS (20%). Furthermore, 3D facial surface scanning proved to be an important noninvasive, diagnostic tool to investigate external features and the underlying skeletal pattern.